Global Problem, Global Language? An Ecolinguistic Analysis of Nationally Determined Contributions Under the Paris Agreement - Chvostek, Ida-Maria (Université d'Ottawa / University of Ottawa, 2023)
Climate change is shaking societal foundations on the deepest level by confronting our relationship with nature, with each other, and even with ourselves. How we handle this situation will not only affect life in the present, but also the future of life. Focusing on the nationally determined contributions (NDCs), national documents outlining mitigation and adaptation efforts reported to the United Nations in accordance with the Paris Agreement of 2015, I have identified several linguistic patterns that I argue not only maintain the status quo but also reinforce the damaging human habits that have created the current crisis. Using discourse, appraisal, and metaphor analysis, I conclude that the prevalent worldview is one of separation. There is a division between nature and humans, where we do not take responsibility for damages inflicted on other lifeforms, as well as between nations and individuals. We also separate emotional from rational thoughts, preferring the latter and shunning the former while telling ourselves a story where humans are still the protagonist. All the while treating nature, along with the negative effects of climate change, as a business opportunity. While these destructive patterns might cast a dark shadow on the future, they also shed light on how we can use language to break away from the mould and create a new narrative through devices such as storytelling, listening, and by actively questioning our interactions with nature. Gradually reconstructing our relationship with the biosphere to become one based on care rather than careless consumption.
Keywords: Climate change; Communication; Emotion; Morals; Linguistics; Eco-linguistics